Effects of a three training models on the development of the situational - motor abilities with handball athletes after conducting 8 weeks of training - Nedelkovski, V.; Strezovski, G.; Kostovski, Z.; Basinac, I. (Sport Science - International Scientific Journal of Kinesiology, 2014)
The research analyzes and compares the changes in specific - motor abilities with young handball athletes. In the experimental procedure were involved 60 subjects, divided into three experimental groups of 20 subjects. An individually targeted program for development of the specific - motor abilities was performed in a period of 8 weeks. The three groups were working on 3 different programs for development of the explosive power of the upper and lower limbs, and the programs were integrated in the usual training process suitable for the competitive period. On this sample were applied 6 specific motor variables associated with the handball game. Starting from the set goals and objectives of the research despite the descriptive statistics, uni variant and multivariate statistical methods were also used. Any differences in the initial and final measuring between one group and between the groups were mutually tested by applying uni variant analysis of the variance (ANOVA), multivariate analysis of the variance (MANOVA) and appropriate LSD - tests (last significant difference). The effects of the programs in the final result and the differences between the groups at the end of the research were determined by multivariate analysis of covariance (MANCOVA) and T - tests for each variable in the initial and final measurement. Statistical analysis showed positive effects of the experimental programs in development of the specific - motor abilities in young handball athletes in all three groups at initial and final measurement.